The ultrasonic changes in maturing placenta in pregnancy complicated with hypertension and its correlation with neonatal outcome - Dutta, Amit; Chatterjee, Kripasindhu; Sen, Sukanta; Ray, Swapan Kumar; Mandal, Pradyut Kumar; Mukhopadhyay, Sima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertension is the most common medical problem encountered during pregnancy, complicating 2-3% of pregnancies. Obstetric ultrasound provides a cornerstone to other modalities used for assessing hypertensive disorders of pregnancy. This study was designed to detect the placental changes in hypertensive disorders of pregnancy and correlation with neonatal outcome. Methods: The study group comprised of 42 patients with pregnancy complicated with hypertension with period of gestation above 20 weeks and B.P. more than 140/90 mm of Hg measured on two occasions 6 hours or more apart. The control group consists of 42 normotensive patients matched with age and parity. One ultrasonic examination were performed between 28 weeks and 34 weeks and another after 34 weeks till term. Apart from routine parameters i.e. BPD, AC, FL, Amniotic fluid index, EBW and gestational age routine placental grading were performed according to the classification proposed by Grannum and associates. To evaluate perinatal outcome following measurement were studied – birth weight immediately after delivery, mode of delivery, perinatal morbidity and mortality , APGAR score , presence of fetal distress. Results: In 97.62% cases (41 out of 42 ) of control group showed Grade–II changes as opposed to 57.14% of cases (24 out of 42) in study group before 34 weeks. Conclusions: Accelerated maturation of placenta in pregnancy complicated with hypertension are more common in the hypertensive group.